Other-initiated repair in interaction between parents and children with repaired cleft lip and/or palate / Mohammad Azannee Saad - Mohammad Azannee , Saad (2019)
Troubles in interaction can negatively impact speakers’ mutual understanding. It is thus necessary for any occurring troubles to be addressed and resolved so speakers understand each other correctly and accomplish successful interaction. One mechanism available for speakers to deal with interactional troubles is other-initiated repair (OIR). OIR is a practice when one speaker initiates repair from speaker of preceding talk that has been treated to be problematic. The success of OIR depends on speakers’ ability to first locate troubles and then initiate repair through necessary strategy. This can help the initiated speaker to respond with necessary repair solution so mutual understanding can be restored. In order for OIR practice to happen smoothly, speakers must be equipped with necessary language, cognitive and social skills. In this study, OIR sequences in everyday interaction between parents and their children with surgically repaired cleft lip and/or palate (CL/P) of Malay backgrounds are analysed. Specifically, this study examines reasons for troubles to occur during interaction, strategies to initiate repair once troubles occur and strategies for repair solution. Examination on OIR sequence includes linguistic and non-linguistic elements that speakers use as resources. Three families that consist of parents and their children with surgically repaired CL/P are recruited for their interaction to be recorded. Recordings of interaction and transcription of verbal data are strictly guided by Conversation Analysis (CA) that serves as this study’s methodological framework. Identification of troubles and coding of repair initiation strategies and repair solution strategies follow coding scheme by Philip (2008). Findings generally show that troubles in interaction occur mostly due to children’s inability to give sufficient information. As a result, parents tend to request for more information thus placing them in a position to initiate repair significantly higher than children. In addition, such children are also identified to have problems in taking turn allocated by others and monitoring topic shift thus resulting in breakdowns. In terms of repair initiation strategy, parents and children are noted to employ a contrasting mechanism; parents employ strategy of requesting for specific information while children employ open-class word to initiate repair from parents. This difference in strategies relates to types of trouble that occur in preceding turn. Finally, repair solution by children is found to be mostly inappropriate. This causes the OIR sequences to be longer when they include many initiations before mutual understanding is achieved. This study has shown the inability for children with surgically repaired cleft to participate in the practice of OIR. In addition, the first language of speakers and their cultural background provide information in the aspect of linguistic and non-linguistic resources of Malay language speakers. Findings of this study contribute to aspect of speech therapy technique to such population with inclusion of pragmatic functioning and to promote parents’ understanding on how to interact with cleft children to ensure their language and social skills develop as normal developing children.